The aggregate and distributional impacts of residence policy relaxation - Tang, Rongsheng (2023)
Government often designs strict policy to control the conversion rate from temporary to permanent residents. The residence status may directly affect individuals’ migration decisions and housing tenure choices. We present a dynamic spatial equilibrium framework to study the aggregate and distributional impacts of residence policy relaxation with a focus on the housing market. The DID approach treating the recent hukou policy reform in China as a shock reveals hukou policy relaxation causes housing prices in the treatment cities to be 4.9% higher than the unaffected cities. The impacts are stronger in cities where obtaining hukou was harder. The model is calibrated to the Chinese economy and predicts that hukou policy relaxation can bring a positive spillover effect to those unaffected cities’ welfare. If hukou policy reform were implemented in those super-mega Chinese cities, housing prices would grow by 2.3%, but the welfare gain equivalent to 3.1% of their current levels.